2017
DOI: 10.3390/app7040345
|View full text |Cite
|
Sign up to set email alerts
|

Pet Fiber Reinforced Wet-Mix Shotcrete with Walnut Shell as Replaced Aggregate

Abstract: Abstract:In the rapidly developing modern society, many raw materials, such as crushed limestone and river sand, which are limited, are consumed by the concrete industry. Naturally, the usage of waste materials in concrete have become an interesting research area in recent years, which is used to reduce the negative influence of concrete on the environment. Hence, this paper presents the development of a sustainable lightweight wet-mix shotcrete by replacing natural coarse gravel with a kind of byproduct, nut … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 54 publications
1
29
0
Order By: Relevance
“…In order to ensure the consistency of experimental variables, PET fibers were cut from the same type bottle of Laoshan mineral water bottle. According to the previous experiments [11,13,17], Young's modulus was 3830 ± 47 MPa, the tensile strength was 108 MPa, and the calculated degree of crystallinity was 23 ± 1%.…”
Section: Pet Fibermentioning
confidence: 80%
See 3 more Smart Citations
“…In order to ensure the consistency of experimental variables, PET fibers were cut from the same type bottle of Laoshan mineral water bottle. According to the previous experiments [11,13,17], Young's modulus was 3830 ± 47 MPa, the tensile strength was 108 MPa, and the calculated degree of crystallinity was 23 ± 1%.…”
Section: Pet Fibermentioning
confidence: 80%
“…Table 2 listed the mix proportion of wet-mix shotcrete. Note that the mixture proportions used in this study were based on practical experiments and literature studies [12,13,54,55].…”
Section: Mixture Composition and Testsmentioning
confidence: 99%
See 2 more Smart Citations
“…According to Joong [19], tunneling shotcrete with 0.6-0.8% volume content of polyamide-fiber-reinforced shotcrete can yield significant improvement in the flexural ductility, toughness, and ultimate load capacity. Cheng [20] reported that fiber addition prevents the formation of plastic shrinkage cracks in underground shotcrete. Yin [21] reviewed that plastic fibers are synthetic fibers, which can be in the form of micro plastic fibers(with the diameter of 5 to 100 µm and length of 5-30 mm) or macro plastic fibers (which have a length of 30-60 mm and cross section of 0.6-1 mm 2 ).…”
Section: Fiber-reinforced Materials and Fiber-reinforced Tslsmentioning
confidence: 99%